(untitled) (Palíndromo, 2020)
I present a reflection on the way in which the ornament appears as a center of interest in a set of works of Roy Lichtenstein, Ana Elisa Egreja and Cristina Iglesias. This analysis allows us to understand how some relations between painting, sculpture and architecture can be proposed, with the ornamental issue as a background. Finally, it presentes a synthesis of conceptual approaches on the theme, developed in the last decade.